The Contemporary Violin: Extended Performance Techniques - Strange, Allen 1943-2008; Strange, Patricia (Berkeley University of California Press, 2001)
Written by a composer and a musician, The Contemporary Violin offers a unique menu of avant-garde musical possibilities that both performers and composers will enjoy exploring. Allen and Patricia Strange's comprehensive study critically examines extended performance techniques found in the violin literature of the latter half of the twentieth century. Drawing from both published and private manuscripts, the authors present extended performance options for the acoustic, modified, electric, and MIDI violin, with signal processing and computer-related techniques, and include more than 400 notated examples. The authors begin with bowing techniques and proceed systematically through other aspects of string playing, including MIDI technologies. Their correspondence and research with many performers and composers, the book's extensive score and text bibliography, and the discography of more than 130 recordings make The Contemporary Violin a valuable contemporary music reference and guide. An additional benefit is its listing of Internet resources that will keep the reader up to date with recent developments in contemporary performance and composition. First published by UC Press, 2001.
Keywords: Violin; Vibrato; Bowing; Fingering; Method